ISLAM & AKTIVITAS PASAR DALAM PERSPEKTIF EKONOMI SYARIAH - Harjoni Desky (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2017)
This article aims to explain the nature of the market mechanism in Islamic economic thought and its practice. Historical and philosophical approach are used in this article to explore the ideas and insights of Muslim scholars on the market. The article concludes that within the framework of Islam, the market mechanism has been considered as an important part of economic activity. According to Islamic economy, market mechanism can occur naturally on the side of supply and demand as it should be. Furthermore, within the mechanism of the market economy perspective of Islam, its principle is to reject the existence of an intervention price if the price changes occur due to normal market mechanisms. However, the market here requires morality, such as: fair competition, honesty, transparency, and justice. If these values have been established, there is no reason to reject the market price. And if there are deviations, the obligation of the state to regulate it for the benefit of the people.